Muon-spin relaxation study of the spin-1/2 molecular chain compound Cu(HCO2)2(C4H4N2) - Lancaster, T; Blundell, S; Brooks, M; Baker, P; Pratt, F; Manson, J; Baines, C (American Physical Society, 2006)
We present the results of a muon-spin relaxation (μ+SR) study of magnetic order in the quasi-one-dimensional spin-1/2 molecular chain compound CU(HCO2)2(C4h4N2). Zero-field μ+SR measurements at low temperatures show oscillations in the measured asymmetry, characteristic of a quasistatic magnetic field at the muon sites. Our measurements provide convincing evidence for long-range magnetic order below a temperature TN=1.97(8) K. This leads to an estimate of the interchain coupling constant of |J'| lkB=1.27 K and to a ratio |J'lJ|=1.6x10-1.